Understanding Moral Psychology in Context: Emotions, Reasoning, and Social Norms - Mudzakkir (Psychosocia : Journal of Applied Psychology and Social Psychology, 2024)
This narrative review explores the psychological foundations of moral decision-making and prosocial behavior by examining the roles of emotion, reasoning, and contextual factors. The objective is to synthesize recent empirical findings to understand how these dimensions interact to influence moral actions. A systematic literature search was conducted using databases such as Scopus, PubMed, and Google Scholar, with keywords including "moral psychology," "prosocial behavior," and "emotional influences on moral reasoning." Inclusion criteria focused on peer-reviewed articles that utilized quantitative, qualitative, or review methodologies and addressed diverse populations across cultures. The results revealed that emotions, particularly empathy and compassion, significantly drive prosocial tendencies, and can be enhanced through interventions like loving-kindness meditation. Moral reasoning is shaped by developmental stages, cultural background, and educational exposure, with deontological and utilitarian frameworks often guiding decisions. Social context, including group identity and societal norms, further modulates moral choices, especially during crises such as the COVID-19 pandemic. These findings align with established theories, including Kohlberg’s moral development stages and contextualist moral models, and highlight the systemic role of education and policy in shaping moral behavior. The review concludes by emphasizing the importance of integrating moral education, promoting emotional development, and implementing inclusive policies to foster prosocial behavior. Future research should prioritize longitudinal and cross-cultural studies to bridge current gaps in understanding the dynamics of moral psychology.